The Association Between Distinct Frontal Brain Volumes and Behavioral Symptoms in Mild Cognitive Impairment, Alzheimer's Disease, and Frontotemporal Dementia - Cajanus, Antti; Solje, Eino; Koikkalainen, Juha; Lötjönen, Jyrki; Suhonen, Noora-Maria; Hallikainen, Ilona; Vanninen, Ritva; Hartikainen, Päivi; de Marco, Matteo; Venneri, Annalena; Soininen, Hilkka; Remes, Anne M.; et al. (Frontiers in Neurology, 2019)
Our aim was to investigate the association between behavioral symptoms of agitation, disinhibition, irritability, elation and aberrant motor behavior to frontal brain volumes in a cohort with various neurodegenerative diseases. A total of 121 patients with mild cognitive impairment (MCI, n=58), Alzheimer’s disease (AD, n=45) and behavioral variant frontotemporal dementia (bvFTD, n=18) were evaluated with a Neuropsychiatric Inventory (NPI). A T1-weighted MRI scan was acquired for each participant and quantified with a multi-atlas segmentation method. The volumetric MRI measures of the frontal lobes were associated with neuropsychiatric symptom scores with a linear model. In the regression model, we included CDR score and TMT B time as covariates to account for cognitive and executive functions. The brain volumes were corrected for age, gender and head size. The total behavioral symptom score of the five symptoms of interest was negatively associated with the volume of the subcallosal area (β=-0.32, p=0.002). High disinhibition scores were associated with reduced volume in the gyrus rectus (β=-0.30, p=0.002), medial frontal cortex (β=-0.30, p=0.002), superior frontal gyrus (β=-0.28, p=0.003), inferior frontal gyrus (β=-0.28, p=0.005) and subcallosal area (β=-0.28, p=0.005). Elation scores were associated with reduced volumes of the medial orbital gyrus (β=-0.30, p=0.002) and inferior frontal gyrus (β=-0.28, p=0.004). Aberrant motor behavior was associated with atrophy of frontal pole (β=-0.29, p=0.005) and the subcallosal area (β=-0.39, p<0.001). No significant associations with frontal brain volumes were found for agitation and irritability. We conclude that the subcallosal area may be common neuroanatomical area for behavioral symptoms in neurodegenerative diseases, and it appears to be independent of disease etiology.